2004
DOI: 10.1063/1.1737368
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-dynamics analysis of the diffusion of molecular hydrogen in all-silica sodalite

Abstract: In order to investigate the technical feasibility of crystalline porous silicates as hydrogen storage materials, the self-diffusion of molecular hydrogen in all-silica sodalite is modeled using large-scale classical molecular-dynamics simulations employing full lattice flexibility. In the temperature range of 700-1200 K, the diffusion coefficient is found to range from 1.6•10 Ϫ10 to 1.8•10 Ϫ9 m 2 /s. The energy barrier for hydrogen diffusion is determined from the simulations allowing the application of transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…[20][21] We have found in previous studies that it is essential to model the framework in a fully flexible manner in order to accurately model the activated diffusion process. 4,12 Alternatively, one could decide to keep the framework rigid; however, our calculations have indicated that this would artificially increase the energy barrier for diffusion by ϳ20% in the case of NaAlSi-SOD, due to the total loss of six-ring flexibility. Furthermore, it would mask any important influences of cation distribution on six-ring flexibility and, thus, diffusion rates ͑vide infra͒.…”
Section: Computational Methodologymentioning
confidence: 96%
See 3 more Smart Citations
“…[20][21] We have found in previous studies that it is essential to model the framework in a fully flexible manner in order to accurately model the activated diffusion process. 4,12 Alternatively, one could decide to keep the framework rigid; however, our calculations have indicated that this would artificially increase the energy barrier for diffusion by ϳ20% in the case of NaAlSi-SOD, due to the total loss of six-ring flexibility. Furthermore, it would mask any important influences of cation distribution on six-ring flexibility and, thus, diffusion rates ͑vide infra͒.…”
Section: Computational Methodologymentioning
confidence: 96%
“…4 All hops that happened within 1 ps of each other were checked manually. A few rapid recrossing events were observed ͑see Table IV͒; however, these were not counted as a hopping event.…”
Section: Computational Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of such centrosymmetric H 2 -H 2 potentials is also evidenced by their use in the setup of high level quantum mechanical calculations of H 2 cluster systems, 11,12 the calculation of the properties of bulk dense H 2 phases, 2,3 and also for larger scale classical molecular dynamics calculations. [13][14][15] More recently the use of density functional theory ͑DFT͒ has been widespread for estimating the properties of H 2 in confined systems. [15][16][17][18][19][20][21] In such studies the binuclear aspect of the H 2 molecule is explicit and the H 2 -H 2 interaction is provided in an ab initio electronic manner albeit indirectly via the choice of functional.…”
Section: Introductionmentioning
confidence: 99%